Strong Exchange Couplings Drastically Slow Down Magnetization Relaxation in an Air‐Stable Cobalt(II)‐Radical Single‐Molecule Magnet (SMM) - Albold, Uta; Bamberger, Heiko; Hallmen, Philipp P.; van Slageren, Joris; Sarkar, Biprajit (Angewandte Chemie International Edition, 2019)
The energy barrier leading to magnetic bistability in molecular clusters is determined by the magnetic anisotropy of the cluster constituents. By incorporating a highly anisotropic four‐coordinate cobalt(II) building block into a strongly coupled fully air‐ and moisture‐stable three‐spin system, it proved possible to suppress under‐barrier Raman processes leading to 350‐fold increase of magnetization relaxation time and pronounced hysteresis. Relaxation times of up to 9 hours at low temperatures were found. A Co production: The energy barrier leading to magnetic bistability in molecular clusters is determined by the magnetic anisotropy of the cluster constituents. By incorporating a highly anisotropic four‐coordinate cobalt(II) building block into a strongly coupled three‐spin system, it proved possible to increase the magnetization relaxation time by a factor of 350 to almost 9 hours at low temperatures.